THE RELATIONSHIP BETWEEN SUPPORT FROM HEALTH WORKERS AND ATTITUDES TOWARDS EXCLUSIVE BREASTFEEDING FOR BREASTFEEDING MOTHERS - Bella Syafira; Sri Mulyani; Lisa Anita Sari; Fadliyana Ekawati; Muthia Mutmainnah (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Breast milk is the optimal source of nutrition for infants, playing a vital role in supporting growth, development, and immunity. Exclusive breastfeeding during the first six months is strongly recommended because it provides important benefits for both infants and mothers. In Indonesia, exclusive breastfeeding coverage reached 68.6% according to SKI 2023 and 74.73% based on BPS 2024, yet these figures remain below the national target of 80%. In Jambi, the coverage is relatively good, although further improvement is still necessary. This study aimed to analyze the relationship between health worker support and mothers’ attitudes toward exclusive breastfeeding in the Pakuan Baru Community Health Center area, Jambi City. A quantitative retrospective cross-sectional design was applied, involving mothers with infants aged 7–12 months selected through random sampling. Data were gathered using questionnaires and analyzed with the Spearman test. The findings showed that support from health workers significantly influenced the success of exclusive breastfeeding practices among mothers.